Governance Challenges for Banten Province's Leadership in 2025 - Nurfaisal, Muhammad Dwi (Pusat Penelitian Ilmu Sosial dan Humaniora Kontemporer, 2024)
The government leadership of Banten Province in 2025 will face significant challenges stemming from the complexities of regional development amid domestic and global transformations. This study examines key issues confronting provincial leaders, including the imperative for transparent governance, political interference-free decision-making, innovation in public service delivery, social conflict management, inter-institutional collaboration, poverty and unemployment alleviation, and evidence-based strategic planning. Employing a descriptive qualitative methodology, this article draws upon relevant academic literature, official government reports, and contemporary news analyses. Effective leadership will play a pivotal role in determining the success of Banten’s governance in 2025, particularly in fostering adaptive and responsive administration under the newly elected governor (2024–2029). Critical to this success is the ability to make policy decisions independent of political pressures, ensuring that governance remains aligned with public welfare. Reflecting on past experiences can provide valuable insights for improving the provincial government’s performance, steering it toward a more community-centric approach.